An essay on the methodology of obligatory prohibition of forbidden trade from the viewpoint of Imam Khomeini - Ã˜Â´Ã›ÂŒÃ˜Â®Ã›ÂŒ Ã™Â†Ã˜ÂµÃ˜Â±Ã˜Â¢Ã˜Â¨Ã˜Â§Ã˜Â¯Ã›ÂŒ, Ã™Â…Ã˜Â¬Ã›ÂŒÃ˜Â¯ Ã˜Â±Ã˜Â¶Ã˜Â§; Ã›ÂŒÃ˜Â²Ã˜Â¯Ã˜Â§Ã™Â†Ã›ÂŒ, Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯ Ã™Â…Ã™Â‡Ã˜Â¯Ã›ÂŒ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
How to deal with the prohibiting forbiddance in the context of trade is the difficult mystery of forbidden professions (makÄsib muharrameh). Some would consider it as an autumn breeze, impeding the thriving transactions of the market; others perceive the encounter of the forbidding prohibition with trade as a collision of two chemicals getting mixed with each other and producing a third material; still others think of this contact as a bomb hitting the bottom of a building totally destroying it and disintegrating its parts. The methodology to identify the prohibition of impermissible trade is the key first step in the study of forbidden professions, including recognition of the subject âthe prohibition of forbidden tradeâ. On the one hand, jurists believe that legally prohibited acts such as wine trade or transactions based on usury are invalid and ownership transfer is thus not achieved; on the other hand, most jurists believe that the obligatory prohibition of these legal exercises entails a specific and independent prohibition. Thus, the challenge of the problem is that it is not clear how a transaction that is invalid and in fact has not happened can ever be forbidden; especially knowing that according to some views, the mere empty give and take does not entail prohibition. The present paper seeks to mention and analyze and critique the viewpoints of jurists. It also aims at collecting prohibited legal actions and relying on Qurâanic verses it tries to derive a correct methodology for identifying independent and non-independent prohibition.